Analysis of factors influencing Work Motivation - Muhammad Immanullah (Universitas Trisakti, 2007)
The objective of this research is to understand if there is influence from mission valence, extrinsic reward toward job difficulty, and job specificity to the mediating variables of job importance and self efficacy in order to increase work motivation on employees of PT Margacipta Wirasentosa in Tangerang, Banten. The research used primary data, simple random sampling in data collection, and multiple regression data analysis method. The result shows that mission valence, extrinsic reward toward job difficulty, and job specificity to the mediating variables of job importance and self efficacy significantly influence work motivation on employees of PT Margacipta Wirasentosa in Tangerang, Banten. Mission socialization is important in order to increase employees work motivation to achieve organization goal. Paradigm change on how job importance is perceived, not only from materials but also rewards, is a must. In order to achieve maximum work result, organization management and eployees must do self-introspection, and understand their capability and skill. In order to force down the gap between employee's capability, skill, and job specification, an excellent job design is a must.